Negative Attitudes of Jews Regarding to Islam and Muslims throughout the History - Yiğitoğlu, Mustafa (Journal of History Culture and Art Research, 2017)
Abstract The topic of this article is the Jewish world’s common view regarding Islam, its Prophet and Muslims dating back from the emergence of Islam to the present day. In this sense, the study sheds light on the history of Jewish thought. Although this investigation cannot be described as a complete analysis on history of thought, the examples which I provide through this article such as negative behaviors of Jewish clergy and other members of Jewish community regarding Islam and Muslims help us to understand the process of this journey. This work investigates Jews’ view on Islam and Muslims and evolution of this thought by examining the statements and texts composed by Jewish clergy against Muslims. By examining a religious group’s ideology throughout the history, this study employs a comparative-historical methodology of ideological practices. The results suggest that the widespread negative attitudes and behaviors of Jewish people regarding Islam and Muslims go back to the times of prophet Mohammad and have fueled during social crises as well as gained momentum in times when social competition was intense.